Product competition, managerial discretion, and manufacturing recalls in the U.S. pharmaceutical industry - Ball, George P.; Shah, Rachna; Wowak, Kaitlin D. (Journal of Operations Management, 2018)
AbstractEmpirical research examining whether and how competition influences product recalls is limited. We address this important research gap by creating a novel measure of product competition using data from the Food and Drug Administration's Orange Book, and combining it with product recall data across a 12‐year period. Our results show that product competition is positively associated with manufacturing‐related recalls, providing evidence of a possible downside to competition in the pharmaceutical industry. Although competition is fostered by numerous federal regulations, we find that it may encourage companies to relax quality standards during the manufacturing process, which may result in lower quality products. We also find that this relationship is contingent on managerial discretion surrounding the recall decision. While product competition is associated with an increase in high severity, low discretion recalls, it is associated with a decrease in low severity, high discretion recalls. Findings from this study have critical implications for policy‐makers who regulate product competition in the pharmaceutical industry.